1989
DOI: 10.1080/00288233.1989.10421751
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolite and hormone concentrations as predictors of genetic merit for lean meat production in sheep: Effects of metabolic challenges and fasting

Abstract: A comparison was made of the responsiveness to metabolic challenges of 10 rams from each of the Massey University High and Low Backfat Southdown selection lines. The lines were established by screening ewes from commercial sources on the basis of high or low weight-corrected backfat depths. Since the initial screening, 2.3 generations of selection have been undertaken, again on the basis of weight-corrected backfat depth (ewes and rams). Progeny of the High Line currently have 47% greater phenotypic backfat de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
2
12
1
Order By: Relevance
“…1987). Weare unable to explain this result but it is worth noting that a postrefeeding rise in growth hormone has been observed in two separate studies of rams from these lines (Carter et al 1989;and this study). It may therefore be a phenomenon peculiar to these inbred lines.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…1987). Weare unable to explain this result but it is worth noting that a postrefeeding rise in growth hormone has been observed in two separate studies of rams from these lines (Carter et al 1989;and this study). It may therefore be a phenomenon peculiar to these inbred lines.…”
Section: Discussionmentioning
confidence: 40%
“…Such responses might potentially be useful as a means of distinguishing between fat and lean genotypes but their repeatability between years remains to be demonstrated. They were not observed by Carter et al (1989) in rams of the two lines SUbjected to a similar nutritional regimen. Growth hormone concentrations were not different between the lines during fasting orrefeeding.…”
Section: Periodmentioning
confidence: 82%
See 1 more Smart Citation
“…Correlations for NEFA and TRIG between the 2 fasting days were lower in magnitude than between feeding and fasting, and conversely for GLUC. The negative correlation between feeding and fasting for NEFA was consistent with selection line differences on each sampling day (Cameron, 1992) (Land et al, 1988 (Bremmers et al, 1988;Carter et al, 1989;Clark et al, 1989; Van Maanen et al, 1989;Cameron, 1992) (1992) reported that log transformations were necessary for NEFA and TRIG, but not for CREA measurements in pigs. In dairy cattle, log transformations of NEFA, TRIG and UREA were required, but not for BHB and GLUC (Woolliams et al, 1992).…”
Section: Statistical Analysesmentioning
confidence: 81%
“…For example, lower urea concentrations have been reported in selection lines of high genetic merit for protein deposition (lean meat or wool) or secretion (milk) than in lines of low genetic merit in sheep (Bremmers et al, 1988;Cameron, 1992;Carter et al, 1989;Clark et al, 1989;Van Maanen et al, 1989), in pigs (Mersmann et al, 1984) and in dairy cattle (Tilakaratne et al, 1980;Sejrsen et al, 1984;Sinnett-Smith et al, 1987).…”
Section: Introductionmentioning
confidence: 99%